BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PERAN IBU DALAM MEMBERIKAN PENDIDIKAN SEKSUALITAS PADA REMAJA DI LINGKUNGAN RESOSIALISASI ARGOREJO KOTA SEMARANG - Dara Fadhillah; Syamsulhuda BM; Kusyogo Cahyo (Jurnal Kesehatan Masyarakat (Undip), 2018)
As much as 7.9% of adolescents who live in the environment of Argorejo Resocialization Semarang city is known to have premarital sexual intercourse. In 2017, 3.2% of STI cases in the Lebdosari Community Health Center area were found in adolescents aged 15-18 years. Adolescents who live in resocial environments are often exposed to these prostitution activities. The influence of the environment can be minimized by providing sexuality education by parents, especially mothers as an effort to prevent premarital sex intercourse. The study aims to analyze mother’s role in providing sexuality education to adolescents in the environment of Argorejo Resocialization Semarang City. The research used cross sectional study design. The population in this research were mothers who had teenage children (10-19 years) and the samples were taken by total population sampling technique which amounted to 49 people. Data analysis used univariate and bivariate analysis. The results of this research showed that the majority of respondents play a role in providing sexuality education in adolescents in the environment of Argorejo resocialization (69.4%). The factors related to the role of mothers in providing youth sexuality education are (p = 0,015), knowledge (p = 0,000) and self efficacy (p = 0,001). Family’s adolescents development group can optimize the role of families, especially mothers in providing sexuality education in adolescents as an effort to prevent premarital sexual intercourse.